1997
DOI: 10.1080/10580539708907042
|View full text |Cite
|
Sign up to set email alerts
|

Issues in Foreign Outsourcing

Abstract: The decision to outsource applications development and support to a foreign vendor involves not only the myriad issues pertinent to outsourcing in general. but a host of additional risks and challenges unique to firms operating in different legal and cultural environments. Careful assessment of these issues helps determine whether offshore outsourcing will realize its potential to reduce costs, improve software quality, and achieve economies of scale in skills acquisition. S~~\ I ) I~R R L \ I A M P Uis ussist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…Somewhat surprisingly, given the nature of outsourcing activities, the following obstacles were ranked lower than other problems in respondents outsourcing efforts: inadequate control systems over how certain services are delivered, which in turn may raise the company's liability exposures (Guterl, 1996), and hidden costs and risks such as travel costs, license transfer fees, exchange rates, and foreign taxes on products and services (Ramarapu et al 1997). In addition, significant was that unsuccessful organizations did not generally consider lack of high-level management support to be a serious problem, which probably means there was support and involvement by top management in these organizations.…”
Section: Achieving Success or Failure Of Outsourcing Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Somewhat surprisingly, given the nature of outsourcing activities, the following obstacles were ranked lower than other problems in respondents outsourcing efforts: inadequate control systems over how certain services are delivered, which in turn may raise the company's liability exposures (Guterl, 1996), and hidden costs and risks such as travel costs, license transfer fees, exchange rates, and foreign taxes on products and services (Ramarapu et al 1997). In addition, significant was that unsuccessful organizations did not generally consider lack of high-level management support to be a serious problem, which probably means there was support and involvement by top management in these organizations.…”
Section: Achieving Success or Failure Of Outsourcing Strategiesmentioning
confidence: 99%
“…Adequate supporting infrastructures, commitment by top management, and development of objective performance criteria were among the factors contributed to successful outsourcing projects. Properly defined performance criteria for an outsourcing engagement are objective, quantifiable, and collectible at a reasonable cost, and should be metrics, which can be benchmarked against performance of other organizations and providers (Ramarapu et al 1997;Kleepes and Jones, 1999). Other factors identified among the top priorities in successful firms include adequate performance feedback, emphasis on both short and long-term benefits, anticipation of change for both good and bad times and accommodation of cycles of demand that require an adjustment in services.…”
Section: Achieving Success or Failure Of Outsourcing Strategiesmentioning
confidence: 99%
“…the fact that an IS function is outsourced to another country actually influences the economic success of an offshore project. Some studies identified various types of risks or challenges associated with offshore outsourcing (Apte et al 1997;Carmel and Agarwal 2002;Khan et al 2003;Kliem 2004;Ramarapu and Parzinger 1997). There is still little understanding, however, about the relationships between offshore-specific challenges, such as cultural differences, geographic distance or regulatory/legal differences, and further economic risks, such as extra costs (Hogan 2004;Barthelemy 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Outsourcing companies occupy a position of power since they control the primary domain knowledge, define the standards of work, and how they should be enforced in practice (Sahay et al 2007). It is often noncore/noncritical and routinized tasks, the non-innovative work, testing and online technical support that is offshored to countries like India (Luftman and Kempaiah 2007;Ramarapu et al 1997). As knowledge is gradually transferred to the contracting company, however, there can be a degree of reconfiguring of the power differential between onshore and offshore companies (Sahay et al 2007).…”
Section: Organizational Change Resistance and Powermentioning
confidence: 99%
“…Recent debates within economic geography have highlighted how space, proximity, and local embeddedness matter for businesses and the process of knowledge formation, learning, and innovation (Amin and Cohendet 2005;Strengers 2014). Different dimensions of distance have often been perceived as inhibiting innovation and growth since they can prevent an efficient flow of information between firm and market (Metters and Verma 2008;Ramarapu et al 1997). The development of trust in business relationships has also been described as requiring spatial proximity, at least initially (Grote and Täube 2006).…”
Section: Offshoring Challenges and Strategiesmentioning
confidence: 99%